Histopathological findings and diagnosis of cutaneous leishmaniasis, confirmed by PCR, in an endemic region of Brazil - Heber P Pena; Vinícius S Belo; Igor dC Fontes; Saulo N de Melo; Paulo HA Soares; Ingrid M Santos; Tiago J Leitão; Maria Zélia dO Costa; Rafael G Teixeira-Neto; Eduardo S da Silva; José Cândido C Xavier-Junior (Journal of Infection in Developing Countries)
Introduction: Diagnosis of cutaneous leishmaniasis (CL) is difficult, and the correct use of histopathological criteria can be useful in clinical practice. The present study evaluates the association between histopathological findings and the results of polymerase chain reaction (PCR) in clinically suspected cases of CL.